Kajian metode uji cepat sebagai metode resmi pengujian kualitas benih tanaman hutan di Indonesia - Muhammad Zanzibar (Badan Standardisasi Nasional, 2009)
Physiological quality is one of the parameter used to determine the seed quality standard in a certification procedure. Information on the physiological quality often not readily available since germination test as a direst test takes time. Rapid test can predict the potency of a seed lot quickly yet accurately but it requires standardization of procedures and interpretation keys. This method relies on the tight correlation between physiological/development of a seed and its viability. In applying a rapid test, the suitability of the test toward the species needs to be determined. Compared to direct test, significant time saving are obtained for 13-34 days with TZ test, 13 – 44 days with cutting test and X-ray test, 7 – 25 days with hydrogen peroxide, 8 – 37 days with excision test and 12 – 19 days with leachate conductivity test. The TZ test and cutting test have been accommodated in the regulation on the physical and physiological test on forestry seeds. The other rapid tests such as excision, hydrogen peroxide, XC-Radiography and leachate conductivity need to be included in that regulation as well. The analyst for the rapid test for this rapid test should be an official that has been certified through intensive training. (peng)